2016
DOI: 10.1002/jrsm.1218
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the biserial correlation and its sampling variance for use in meta‐analysis

Abstract: Meta-analyses are often used to synthesize the findings of studies examining the correlational relationship between two continuous variables. When only dichotomous measurements are available for one of the two variables, the biserial correlation coefficient can be used to estimate the product-moment correlation between the two underlying continuous variables. Unlike the point-biserial correlation coefficient, biserial correlation coefficients can therefore be integrated with product-moment correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…The point biserial correlation and phi correlation coefficients obtained by converting from artificially dichotomized data are not comparable with Pearson’s product moment correlations, and should not be combined in the same meta‐analyses 44 . Another index, the biserial correlation coefficient, estimates the underlying continuous relationship between a continuous variable and an artificially dichotomized one, and can be synthesized with the Pearson's product moment correlation for the purposes of meta‐analysis 44 . The point biserial correlation calculated from artificially dichotomized data is always less than 80% of the biserial correlation 47 .…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The point biserial correlation and phi correlation coefficients obtained by converting from artificially dichotomized data are not comparable with Pearson’s product moment correlations, and should not be combined in the same meta‐analyses 44 . Another index, the biserial correlation coefficient, estimates the underlying continuous relationship between a continuous variable and an artificially dichotomized one, and can be synthesized with the Pearson's product moment correlation for the purposes of meta‐analysis 44 . The point biserial correlation calculated from artificially dichotomized data is always less than 80% of the biserial correlation 47 .…”
Section: Methodsmentioning
confidence: 98%
“…The point biserial correlation explores the relationship between a continuous and a dichotomous variable 44 . This correlation may be encountered when studies dichotomize DUP into long/short, or if DUP remains continuous and the outcome is either naturally dichotomous (completed suicide) or artificially dichotomous (high/low symptom scores).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three out of five included studies poorly reported their statistical parameters, and thus, we decided to estimate the means from the provided figures and standard deviations for means of outcome value by using the coefficient of variance (CV) (Jacobs and Viechtbauer, 2017). After excluding studies with imputed standard deviations for all different outcome parameters, the estimates were reasonably robust for standard deviation imputation.…”
Section: Data Synthesismentioning
confidence: 99%
“…This paragraph introduces the syntax and usage of VARA function in Microsoft Excel. VARA function calculates the variance of the given sample, using method as follows [6] if the parameters that contain text or FALSE are evaluated as 0 (zero). 5. if the parameter is an array or reference, only ues the value of parameter.…”
Section: Vara Functionmentioning
confidence: 99%